(untitled) (Fiep Bulletin - online, 2014)
The diving is a standalone activity held in wild environment. There are indications that psychological factors influence and are influenced by physical activities, creating therefore influence over the operation of diving. This research was aimed at mapping out the psychological profile of divers standalone during their performance in order to better understand what type of individual is dedicated to the activity. For the analysis of this profile, was used an inventory developed by Loehr (1982) and validated by Raposo (1993) which aims to identify seven psychological variables of performance through the 42 questions that are answered in a kind likert scale of 5 points. In descriptive analysis of the psychological variables has been observed: self confidence (25,90 ± 2,62); Control of negativism (21,63 ± 1,62); Focus atencional (19,09 ± 2.19); View (17,11 ± 2,27); motivation (23,47 ± 2,83); good thoughts (18,97 ± 2,03); attitude competitive (21,63 ± 2,22). The strongest feature of the personality of individuals in the group was a self confidence.